ASSOCIATION BETWEEN FREQUENCY OF PHYSICAL EDUCATION CLASSES AND HEART RATE VARIABILITY IN ADOLESCENTS BOYS: A CROSS-SECTIONAL STUDY - Jéssika Karla Tavares do Nascimento Faustino da Silva; Ozeas de Lima Lins Filho; Antonio Henrique Gernmano-Soares; Raphael Mendes Ritti-Dias; Breno Quintella Farah (Journal of Physical Education)
ABSTRACT Physical inactivity is associated with low heart rate variability (HRV) in adolescents. However, whether the number of physical education (PE) classes impact HRV remains unclear. This cross-sectional study verified the association between the frequency of PE classes and HRV parameters in male adolescents. This study included 1152 boys (16.6 ± 1.2 years). The quantity of PE classes was assessed though questionnaire and the adolescents were stratified accordingly (no PE class; one PE class/wk; ≥2 PE classes/wk). Time- (SDNN, RMSSD, PNN50) and frequency-domains (LF, HF, sympathovagal balance) of HRV were obtained. Generalized Linear Models were used for comparing the HRV parameters according to the quantity of PE classes, adjusting for confounders. There was no difference in HRV measures of time: (SDNN, p = 0.77; RMSSD, p=0.72; PNN50, p=0.83) and frequency (LF, p=0.61; HF, p=0.61; sympathovagal balance, p=0.60) between the different frequencies of PE classes. The frequency of PE classes in not associated with HRV parameters of male adolescents.